Adult phenotype of KCNQ2 encephalopathy. Issue 6 (2nd April 2021) - Boets, Stephanie; Johannesen, Katrine M; Destree, Anne; Manti, Filippo; Ramantani, Georgia; Lesca, Gaetan; Vercueil, Laurent; Koenig, Mary Kay; Striano, Pasquale; Møller, Rikke Steensbjerre; Cooper, Edward; Weckhuysen, Sarah
Abstract : Background: Pathogenic KCNQ2 variants are a frequent cause of developmental and epileptic encephalopathy. Methods: We recruited 13 adults (between 18 years and 45 years of age) with KCNQ2 encephalopathy and reviewed their clinical, EEG, neuroimaging and treatment history. Results: While most patients had daily seizures at seizure onset, seizure frequency declined or remitted during childhood and adulthood. The most common seizure type was tonic seizures (early) infancy, and tonic-clonic and focal impaired awareness seizures later in life. Ten individuals (77%) were seizure-free at last follow-up. In 38% of the individuals, earlier periods of seizure freedom lasting a minimum of 2 years followed by seizure recurrence had occurred. Of the 10 seizure-free patients, 4 were receiving a single antiseizure medication (ASM, carbamazepine, lamotrigine or levetiracetam), and 2 had stopped taking ASM. Intellectual disability (ID) ranged from mild to profound, with the majority (54%) of individuals in the severe category. At last contact, six individuals (46%) remained unable to walk independently, six (46%) had limb spasticity and four (31%) tetraparesis/tetraplegia. Six (46%) remained non-verbal, 10 (77%) had autistic features/autism, 4 (31%) exhibited aggressive behaviour and 4 (31%) destructive behaviour with self-injury. Four patients had visual problems, thought to be related to prematurity in one. Sleep problems were seen in six (46%) individuals. Conclusion: Seizure frequency declines over the years and most patients are seizure-free in adulthood. Longer seizure-free periods followed by seizure recurrence are common during childhood and adolescence. Most adult patients have severe ID. Motor, language and behavioural problems are an issue of continuous concern.